Transcription factors—Intricate players of the bone morphogenetic protein signaling pathway. Issue 1 (27th September 2017) - Ampuja, M.; Kallioniemi, Anne
Abstract: Bone morphogenetic proteins (BMPs) are a family of growth factors, some of which are known by the name growth and differentiation factor (GDF). BMPs were discovered in the 1960s in an attempt to find factors capable of inducing bone formation. By the end of 1980s, several different BMPs had been found and to date, around 20 members are known. Together with TGFβ, nodal, and activins, they comprise the TGFβ superfamily. BMPs are known to regulate cell fate both in development and adult tissues, and as such they are also involved in many disease states. Understanding the impact of BMPs in these processes requires intimate knowledge of the regulation of the BMP signaling pathway. The intracellular BMP pathway has been studied extensively but the various transcription factors (TFs) necessary for the BMP‐mediated gene expression changes have remained under less scrutiny. Most of the studies have focused on specific TFs in the context of differentiation or development. Varying cell types and BMPs have been used, but no large‐scale studies have yet been performed. Here we aim to summarize the current knowledge on BMP pathway‐related TFs, focusing on those involved in the canonical BMP signaling pathway through the SMAD proteins.